(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Retribution is a potential source of potential local revenue because the scope of imposition of regional retribution more widely than the local taxes. Development of regional retribution is easier compared to local taxes since the scope of imposition of regional retribution is not as restrictive as compared to local taxes. Therefore, local governments in order to develop local revenues are more focused on efforts to increase the acceptance of regional retribution.This study aims to determine the implementation of the policy on the management of levy of the market in support of local revenue in the district of Morotai Island.This research uses descriptive qualitative approach by describing the data obtained from the result of the research on policy implementation the management of leevy of the market in support of local revenue. The subject of this research is the employees of the department of perindakop and smes and the market traders. In qualitative research data collection is done by observation, interview, and documentation and data analysis technique consist of data reduction, data presentation and withdrawal of conclusion/verification. Policy implementation the management of levy of the market in support of local revenue in the district of Morotai Island for the moment this is not optimal as seen from the indicators of the content of policy and the implementation environment is still far espected as well as the lack of attention from the government especially in the implementation of market retribution policy Keyword: Policy Implemetation, Market Levy